2016
DOI: 10.1007/s00259-016-3595-y
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the actual I-131 thyroid uptake curve with a collar detector system: a feasibility study

Abstract: Radionuclide therapy using I-131 is commonly used for the treatment of benign thyroid diseases. The therapeutic dose to be administered is calculated based on the type of disease, the volume of the thyroid, and the measured uptake percentage. This methodology assumes a similar biological half-life of iodine, whereas in reality a large variation in biological half-life is observed. More knowledge about the actual biological half-life of iodine for individual patients will improve the quantification of the deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…In that initial study, the repeated measurements by a phantom (for I-123) showed a mean sensitivity of 2.2 × 102 (± 15) cps/MBq with a good precision of 7% 4 . The coefficient of determination between the COTI measured values and the standard gamma probe was 0.87, confirming the excellent correlation between the two methods 4 . For I-131, there was an uncertainty of 3%, and a correction factor above 2000 counts per second was recommended.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…In that initial study, the repeated measurements by a phantom (for I-123) showed a mean sensitivity of 2.2 × 102 (± 15) cps/MBq with a good precision of 7% 4 . The coefficient of determination between the COTI measured values and the standard gamma probe was 0.87, confirming the excellent correlation between the two methods 4 . For I-131, there was an uncertainty of 3%, and a correction factor above 2000 counts per second was recommended.…”
Section: Discussionmentioning
confidence: 92%
“…Previous work on COTI has involved demonstrations of the technique's feasibility and comparability with the standard uptake probe. In the study by Brinks et al, reproducibility, linearity, and accuracy measurements using both I-123 and I-131 radiotracer were performed 4 . In that initial study, the repeated measurements by a phantom (for I-123) showed a mean sensitivity of 2.2 × 102 (± 15) cps/MBq with a good precision of 7% 4 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The device is described in detail in Ref. Acquisitions are initiated by the patient by pressing a large button on a second device, which is wirelessly connected to both the acquisition unit and the Internet. The latter option allows for remote monitoring of the measurements.…”
Section: Methodsmentioning
confidence: 99%